2005
DOI: 10.1021/bc050050z
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Conjugated Iron Oxide Nanoparticles for Solid Tumor Targeting as Potential Specific Magnetic Hyperthermia Mediators: Synthesis, Physicochemical Characterization, and in Vitro Experiments

Abstract: New folate-conjugated superparamagnetic maghemite nanoparticles have been synthesized for the intracellular hyperthermia treatment of solid tumors. These ultradispersed nanosystems have been characterized for their physicochemical properties and tumor cell targeting ability, facilitated by surface modification with folic acid. Preliminary experiments of nanoparticles heating under the influence of an alternating magnetic field at 108 kHz have been also performed. The nanoparticle size, surface charge, and coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
321
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(326 citation statements)
references
References 29 publications
4
321
0
1
Order By: Relevance
“…The treatment period was ∼3 h. Cells were irradiated as described in the irradiation methods; control cells accompanied the irradiated cells to and from the X-ray machine. Irradiated cells were dissociated and combined for each treatment type, counted (using a Coulter Counter Z1 instrument from Beckman Coulter for experiments 1-11 and an Auto T4 instrument from Nexcelom Bioscience for experiments [12][13][14][15][16][17], and then reseeded in a six-well plate. Two hundred cells per well were seeded for 0-and 1.5-Gray radiation doses, and 500 cells per well were seeded for 3-Gray radiation dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment period was ∼3 h. Cells were irradiated as described in the irradiation methods; control cells accompanied the irradiated cells to and from the X-ray machine. Irradiated cells were dissociated and combined for each treatment type, counted (using a Coulter Counter Z1 instrument from Beckman Coulter for experiments 1-11 and an Auto T4 instrument from Nexcelom Bioscience for experiments [12][13][14][15][16][17], and then reseeded in a six-well plate. Two hundred cells per well were seeded for 0-and 1.5-Gray radiation doses, and 500 cells per well were seeded for 3-Gray radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies have raised serious questions about the efficacy of targeting ligands on nanoparticle accumulation in tumor tissues. Multiple reports have shown that targeted nanoparticles did not lead to increased tumor accumulation over nontargeted controls, although increased cellular uptake was observed in each case (12)(13)(14). In addition, histologic studies showed that antibodies conjugated with gold nanoparticles do not penetrate deeply into tumors, but mostly stain peripheral tumor regions (15).…”
mentioning
confidence: 93%
“…The effective binding and tumor growth inhibition of SPIOanti-Her2-AB against breast cancer cells (SKBr3) [203], of anti-EGFRvIII-SPIO against glioblastoma cells [204], or of cetuximab-anti-EGFR immunomicelles against A431 malignant cells [205] was shown in the first approach. The second strategy was able to be successfully shown by binding magnetoliposome-antibody complexes to MN antigens of renal cell carcinoma cells [206], magnetoliposomeanti-Her2-AB to breast cancer cells [203], or anti-folate receptor-SPIO to different tumor cell lines [207]. The third strategy was able to be successfully proven on the basis of rhenium188-loaded immuno(hepama-1)magnetic nanoparticles (Re-SPIO-AB) against liver carcinoma cells [208], methotrexate-conjugated SPIO against breast (MCF7) and cervical (HeLa) carcinoma cells [209], doxorubicin-loaded nanomicelles [210], doxorubicin-carrying hyaluronan-SPIO (DOX-HA-SPIO) [211], docetaxel-carboxymethylcellulose-SPIO [212], layer-by-layer (LbL) polyelectrolyte capsules that can be loaded with SPIO and/or therapeutic agents [213], SPIO-and doxorubicin-loaded cetuximab-anti-EGFR immunomicelles or with doxorubicin(liposomal)-loaded macrophages (macrophage-LP-Dox) that accumulate in tumors [214].…”
Section: Molecular Therapymentioning
confidence: 99%
“…However it should be underlined that knowing the safe upper limit of the safe use of SPIONs is of great importance (Gupta & Curtis, 2004;Sonvico et al, 2005). Since their discovery, nanoparticulate drug-delivery systems based on magnetic iron oxide nanoparticles have become an attractive and challenging field of research Pankhurst et al, 2003), but even though there are fascinating changes happening almost every day, there is still much uncertainty and issues regarding toxicity (Mahmoudi et al, 2011a;Laurent et al, 2011), biocompatibility or targeting efficiency and accumulation in RES (reticuloendothelial system) to be explained (Sharifi et al, 2012).…”
Section: Motivationmentioning
confidence: 99%